p38-MAP Kinase Negatively Regulates the Slow Force Response to Stretch in Rat Myocardium through the Up-Regulation of Dual Specificity Phosphatase 6 (DUSP6) - Zavala, Maite Raquel (2019)
Background/aims: Myocardial stretch increases cardiac force in two consecutive phases: The first one due to Frank-Starling mechanism, followed by the gradually developed slow force response (SFR). The latter is the mechanical counterpart of an autocrine/paracrine mechanism involving the release of angiotensin II (Ang II) and endothelin (ET) leading to Na⁺/H⁺ exchanger 1 (NHE-1) phosphorylation and activation. Since previous evidence indicates that p38-MAP kinase (p38-MAPK) negatively regulates the Ang II-induced NHE1 activation in vascular smooth muscle and the positive inotropic effect of ET in the heart, we hypothesized that this kinase might modulate the magnitude of the SFR to stretch. Methods: Experiments were performed in isolated rat papillary muscles subjected to sudden stretch from 92 to 98% of its maximal length, in the absence or presence of the p38-MAPK inhibitor SB202190, or its inactive analogous SB202474. Western blot technique was used to determine phosphorylation level of p38-MAPK, ERK1/2, p90RSK and NHE-1 (previously immunoprecipitated with NHE-1 polyclonal antibody). Dual specificity phosphatase 6 (DUSP6) expression was evaluated by RT-PCR and western blot. Additionally, the Na⁺-dependent intracellular pH recovery from an ammonium prepulse-induced acid load was used to asses NHE-1 activity. Results: The SFR was larger under p38-MAPK inhibition (SB202190), effect that was not observed in the presence of an inactive analogous (SB202474). Myocardial stretch activated p38-MAPK, while pre-treatment with SB202190 precluded this effect. Inhibition of p38-MAPK increased stretched-induced NHE-1 phosphorylation and activity, key event in the SFR development. Consistently, p38-MAPK inhibition promoted a greater increase in ERK1/2-p90RSK phosphorylation/activation after myocardial stretch, effect that may certainly be responsible for the observed increase in NHE-1 phosphorylation under this condition. Myocardial stretch induced up-regulation of the DUSP6, which specifically dephosphorylates ERK1/2, effect that was blunted by SB202190. Conclusion: Taken together, our data support the notion that p38-MAPK activation after myocardial stretch restricts the SFR by limiting ERK1/2-p90RSK phosphorylation, and consequently NHE-1 phosphorylation/activity, through a mechanism that involves DUSP6 up-regulation.